PENERAPAN ALGORITMA PROBABILISTICLATENT SEMANTIC INDEXING UNTUK MENDETEKSI DUPLIKASI JURNAL DI STIKI MALANG - Kartikasari, Meivi (DINAMIKA DOTCOM, 2018)
The Â impact of the development of information technology and computerization is to make easier for writers to compose a paper of scientific writing. This has an impact on the possibility of increased plagiarism. Such actions may harm the original author and plagiarist. The manual plagiarism detection process is difficult because of the large number of manuscripts, so needed the system to detect plagiarism. To build a system that can detect plagiarism, certain algorithms are needed to measure the value of similarities between the documents compared. One of the algorithms used to detect similarities is Probabilistic Latent Semantic Analysis (PLSA). This method uses the term value reference and the result of singular value decomposition (SVD) to know the closeness between documents so that it can be known the value of similarity between documents.Â Keywords: Similarity, Probabilistic Latent Semantic Analysis,Singular Value Decompositio